Pengaruh Dukungan Sosial Terhadap Kesejahteraan Psikologis Pada Mahasiswa Semester Akhir - Desi Alawiyah; Citra Anggraeni Alwi; Lilis; Selvi (Institut Agama Islam Muhammadiyah Sinjai, 2022)
Psychological Well Being is a biological well-being characterized by self-acceptance, positive correlation, independence, environmental dominance, purpose in life, and self-development. In the Covid-19 era, this has a big impact on life, especially for final semester students, with the Large-Scale Social Restrictions (PSBB) which harms many parties, especially those who are forced to carry out three higher education services and are unable to carry out Compulsory Student Education. Business as usual in education, research and community service. Delayed, in addition to the burden of the final task which becomes an obstacle for students, it is also difficult to write papers, mentoring, etc., which is a challenge that has a lot of negative impacts on the psychology of final students. The emergence of psychological barriers, resulting in the welfare (Psichological Well Being) of students in the learning process is hampered. Student mental health is related to academic ability and how their relationship uses social skills, health, and spirituality. Efforts to create an environment that supports the mental health of students must have good social support. Social support comes from family, friends, friends and social groups.